The Naming of Hosts Is a Difficult Matter. - Neville-Neil, George V. (Communications of the ACM, 2013)
The article presents questions and answers related to computer programming including how to decide on a host-naming scheme and how to explain to an employee that some information needs to be collected in a case of system misbehavior that is vital to the resolution of the problem.